The underlying values of the national core curriculum in upper elementary English teaching - Hanhivaara, Tuomas (2018)
The purpose of this study was to investigate how the underlying values of the National Core Curriculum for Basic Education 2014 were viewed by English language teachers in Finnish upper elementary schools and how they applied the underlying values in their English teaching. Four teachers were interviewed separately in a semi-structured interview. The interviews were recorded, transcribed, and analysed with content analysis.